(untitled) (Transport systems and technologies, 2023)
This study tackles the complex task of constructing a dynamic model of a navigator, planning their experience trajectory, and making decisions under navigational risks in the maritime industry using automated control systems. the proposed mathematical model accounts for individual skills, experiences, and personalities, while considering unpredictable industry dynamics. the study asserts the importance of adaptable automated control systems capable of simulating navigation risk situations and determining suitable career and development paths. in addition, it discusses the importance of assessing external factors such as economic, technological, and regulatory changes and ensuring compliance with industry standards, data security, and privacy. the paper further emphasizes the necessity for scalability and flexibility, as well as the seamless integration of automated systems with existing organizational infrastructures. the study concludes that the proposed model, optimized for the "safety of navigation" parameter using the Pontryagin maximum principle, enhances recruitment processes, creates comprehensive professional profiles for seafarers, and supports career development. the paper suggests the potential of this model’s application in other maritime and related professions, ultimately enhancing individualized training and operational efficiency.